Studying the decontamination process of an irradiated beryllium reflector in a chlorine environment. - Yuliya Baklanova (PLoS ONE)
Beryllium, possessing unique nuclear physical properties, is currently widely used as a material for reflector and neutron moderator blocks of research nuclear reactors. It can also be applied in fusion energy as a first-wall material and neutron multiplier. However, when beryllium is irradiated, its physical-mechanical properties deteriorate due to radiation-induced microstructural damage, the generation of tritium and helium, the activation of impurities under the radiation exposure, and the absorption of fission products, which determines the need for periodic replacement of the beryllium components in nuclear installations. Moreover, due to the relatively low abundance of beryllium, a relevant problem is its purification from radioactive isotopes for potential reuse. To date, chlorination has emerged as one of the most promising methods for purifying irradiated beryllium. This study addresses the optimization of the chemical process parameters and the isolation of the beryllium component from the resulting mixture of chlorination products, including the most active radionuclides: 3H, 60Co, 108mAg, and 137Cs. Laboratory-scale experiments confirmed the effectiveness of the irradiated beryllium chlorination technology for its purification. The reduction in the activity level of beryllium and its compounds was objectively monitored using gamma and beta spectrometry methods.